VoIP Data Transmission System Based on G.729A - Shen, Yan Chun (Applied Mechanics and Materials, 2013)
It uses Windows low-level audio API to record and broadcast voice packets, encodes and decodes through G.729A, and groups by TCP/IP protocol, transmits data packets by UDP on the SOCK_DGRAM SOCKET between the client and the server, So as to achieve the function of Internet voice communication. To ensure user friendly interface, the premise here using multi-threaded programming. In addition, the system also in application-layer protocol adds the text chat function which based on TCP transmission. The essence of the design is to realize software to communicate by voice or text which based Windows operating system. The successful debugging of this software will have a positive effect on the PC to PC kind of VoIP communications system.